EFEKTIFITAS PERAN PENYULUH PADA PENDAMPINGAN PENERIMA PERSETUJUAN PENGELOLAAN PERHUTANAN SOSIAL DI UPTD KPH TERNATE-TIDORE (HKm Ake Guraci) - Muhidin, Fadli; Kurniawan, Andy; Hadun, Ramli; Ryadin, Aisjah Rahmawaty; Umasugi, Buhari; Sapsuha, Yusri (Jurnal Pertanian Khairun, 2025)
The role of forestry extension workers is crucial for the success of social forestry programs, particularly in empowering communities to manage forest resources sustainably. This study evaluates the effectiveness of forestry extension workers in assisting recipients of social forestry management approval in the HKm Ake Guraci group, focusing on their role as facilitators, educators, communicators, and motivators. Data was collected through interviews, surveys, and field observations. The effectiveness of assistance was evaluated based on three key areas: institutional management, area management, and business management. Results show high effectiveness in institutional management (82%), area management (80.2%), and business management (79.6%). Recommendations include improving document processing times, enhancing training, and strengthening marketing strategies for forest-based products